Mechanical/Structural Properties of Ag, Cu, and Ni Thin Films. (1st January 2017) - Mohammed, Yousuf S.; Baumgart, Helmut; Elmustafa, A. A.
Abstract : Metallic films of Ag, Cu, and Ni, each of four different thicknesses (150, 300, 600 and 1000 nm) were deposited on Si using E-beam evaporation. A shutter was used to successively cover increments of 1 ″ of the wafer at a time, starting with the wafer fully uncovered. A thin titanium layer of 10 nm is first deposited over the entire Si wafers followed by 150, 300, 600, and 1000 nm of the 2 ″ target material. Vacuum conditions at the start were ∼1 × 10 −7 torr and reached as high as 2 × 10 −6 torr during the copper deposition due to outgassing. The structural and surface properties were explored using field emission scanning electron microscopy (FE-SEM) and atomic force microscopy (AFM). The nanomechanical properties were measured using nanoindentation to determine the modulus and hardness of the Ag, Cu, and Ni films. Nanocrystalline grain structure formation is observed to dominate the crystal film growth. The hardness increases as the film thickness decreases, and remains nearly flat with depth for the same film, except for the very thin films as they suffer from what is known as the tapping effect.